Fertilisation and early embryonic development of immature and rescue in vitro-matured sibling oocytes. (1st January 2022) - Avci, Berrin; Kasapoglu, Isil; Cakir, Cihan; Ozbay, Aysun; Ata, Baris; Uncu, Gurkan
Abstract: The objective of this study was to assess the effect of rescue in vitro maturation and immediate intracytoplasmic sperm injection (ICSI) application on fertilisation success and early embryonic development of metaphase I (MI) oocytes. This was a retrospective cohort study including 2425 sibling oocytes in 259 ICSI cycles. ICSI was performed on 104 GV (germinal vesicle) oocytes which had reached the metaphase II (MII) stage (Group 1) and 231 MI oocytes which had reached the MII stage (Group 2) following IVM (in vitro maturation). Immediate ICSI was applied following oocyte aspiration on 292 MI stage (Group 3) and 1798 MII stage oocytes (Group 4). Normal fertilisation rates in Groups 1, 2, 3 and 4 were 51.9%, 39%, 30.1% and 59.5%, respectively. The rates of blastocyst development per oocyte and per zygote were calculated as 3.8%, 3.0%, 6.8%, 14.1% and 7.4%, 7.7%, 22.7%, 23.6% for Groups 1, 2, 3 and 4, respectively. The blastocyst development rate was significantly higher in the MI-ICSI group compared with other immature oocytes. Even though performing ICSI on the oocytes at the MI stage on the day of oocyte aspiration resulted in lower fertilisation rates, it was associated with significantly higher rates of blastocyst development.